2001
DOI: 10.1038/sj.ijir.3900706
|View full text |Cite
|
Sign up to set email alerts
|

Ferula harmonis ‘zallouh’ and enhancing erectile function in rats: efficacy and toxicity study

Abstract: Ferula harmonis, which is locally called`zallouh' in the Middle East, is used as an aphrodisiac as it is reputed to enhance male sexual behavior, however, there is no scienti®c veri®cation. In this study, the oil extracted from the seeds of Ferula harmonis was tested for its ef®cacy in enhancing erectile function and toxicity in male rats. The sexual activities assessed by penile erection index were dose dependent. The ED 50 (12.03 mgakg) was 880 times less than the LD 50 (10.6 gakg). However, when doses rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 10 publications
0
38
0
1
Order By: Relevance
“…Copulatory behavior of male rats P Zanoli et al A previous study revealed that F. hermonis seed oil was able to stimulate erectile function. 6 In our study, Ferula acetonic extract significantly enhanced male sexual appetitive behavior in potent rats, as evidenced by reduced mount and intromission latencies in comparison with controls. These parameters are indeed considered to be inversely proportional to sexual motivation or desire.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Copulatory behavior of male rats P Zanoli et al A previous study revealed that F. hermonis seed oil was able to stimulate erectile function. 6 In our study, Ferula acetonic extract significantly enhanced male sexual appetitive behavior in potent rats, as evidenced by reduced mount and intromission latencies in comparison with controls. These parameters are indeed considered to be inversely proportional to sexual motivation or desire.…”
Section: Discussionmentioning
confidence: 91%
“…The development of the method could be of importance in the quality control of products containing F. hermonis, which are emerging in the dietary supplement market. 5 A recent study performed with the aim of clarifying the efficacy and the safety of this plant was published by El-Thaher et al 6 The authors demonstrated the capacity of the crude oil extracted from the seeds of F. hermonis, when administered acutely in rats, to enhance erectile function. On the contrary, when chronically administered, it exerted unwanted and toxic effects such as decrease in total body weight, hepatomegaly and atrophic testis.…”
Section: Introductionmentioning
confidence: 99%
“…1 The enhancement of erectile function after oral ingestion of the crude oil extracted from the seeds of F. hermonis was observed in rats by ElThaher et al 2 On the other hand, the daily administration of the oil for 28 days was linked to toxic effects such as decreased body weight, hepatomegaly, atrophic testis, significant decrease in hemoglobin and red blood cells. 2 Moreover, an antifertility effect of the ethanolic extract obtained by F. hermonis roots, orally administered for 6 weeks to male and female mice, was reported. 3 It is noteworthy, however, that depending on the type of solvent used for the extraction procedure, F. hermonis exerted different effects on male rat sexual activity.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 PEI improved with increasing dose. Maximum PEI values were obtained at the maximum dose of 0.625 mg=kg body weight for both drugs.…”
Section: Effect On Male Rat Erectile Responsementioning
confidence: 94%